Análisis de la planta turística ocio y recreación del cantón Sigchos provincia de Cotopaxi - Icaza Iza, Eslendy Karina (2021)
The present research project is about the leisure and recreation tourism plant of the Sigchos canton, for its development 3 specific objectives were proposed. In the first objective, the current situation of the Sigchos canton was determined and the tourism system was analyzed through a bibliographic review of; research, books, Web pages, articles or theses related to the problem under study, development plan of territorial planning PDOT, GAD of Sigchos, using the analytical method which consists of the separation of a whole for the understanding of the same. In the second objective, the tourist attractions were inventoried by means of interviews with the director of tourism, owners or workers of the tourist, natural, cultural and tourist establishments using the tourist plant of leisure and recreation created by the career of Tourism, which corresponds to the survey and registration of tourist attractions that allowed identifying 11 tourist attractions in the Sigchos parish, 6 in the Chugchilan parish, 2 in the Isinliví parish, 2 in the Las Pampas parish, 2 in the Palo Quemado parish. In total there were 23 tourist attractions, 11 natural sites, 5 churches, 4 inns, 1 campground, 1 park, 2 fairs, 1 wine factory, depending on their characteristics, different recreational options could be carried out, such as agrotourism, adventure tourism and cultural tourism. Finally, for the third objective where all the information collected was systematized in the design of the catalog, it was through instruments and techniques such as the computer, cell phone, Photoshop and the illustrator program, a catalog was obtained in which the information of the Sigchos canton was captured, to make it known to domestic and foreign tourists.